2018
DOI: 10.1038/s41591-018-0048-0
|View full text |Cite|
|
Sign up to set email alerts
|

Inactivating hepatic follistatin alleviates hyperglycemia

Abstract: Unsuppressed hepatic glucose production (HGP) contributes significantly to glucose intolerance and diabetes, which can be modeled by genetic inactivation of hepatic insulin receptor substrate (Irs) 1 and Irs2 (LDKO-mice). We previously showed that glucose intolerance in LDKO-mice is resolved by hepatic inactivation of the transcription factor FoxO1 (i.e., LTKO-mice)—even though the liver remains insensitive to insulin. Here, we report that insulin sensitivity in the white adipose tissue (WAT) of LDKO-mice is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
115
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(129 citation statements)
references
References 54 publications
7
115
6
1
Order By: Relevance
“…As recently reported, FST inactivation improves glucose tolerance in hyperglycaemic mice, and FST levels decreased in parallel with HbA1c in 10 morbidly obese individuals with T2D after RYGB . In our study, we observed a significant reduction in FST after both RYGB and VSG, but not after AGB.…”
Section: Discussionsupporting
confidence: 43%
See 4 more Smart Citations
“…As recently reported, FST inactivation improves glucose tolerance in hyperglycaemic mice, and FST levels decreased in parallel with HbA1c in 10 morbidly obese individuals with T2D after RYGB . In our study, we observed a significant reduction in FST after both RYGB and VSG, but not after AGB.…”
Section: Discussionsupporting
confidence: 43%
“…Follistatins participate in a wide spectrum of physiological processes, ranging from reproductive function to muscle and liver metabolism, as well as glucose and lipid homeostasis . It has been reported recently that knockdown of FST in hyperglycaemic mice improves glucose tolerance by increasing white adipose tissue insulin sensitivity and by reducing hepatic glucose output . In addition, circulating FST concentrations were elevated in patients with type 2 diabetes (T2D) and decrease concomitantly with HbA1c in a limited number of obese individuals with T2D 6 months after Roux‐en‐Y gastric bypass (RYGB) .…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations